Solving Schrödinger equation for two dimensional potential using supersymmetry - Drigo Filho, Elso [UNESP] (Editora Unesp, 1997)
The formalism of supersymmetric Quantum Mechanics can be extended to arbitrary dimensions. We introduce this formalism and explore its utility to solve the Schodinger equation for a bidimensional potential. This potential can be applied in several systens in physical and chemistry context, for instance, it can be used to study benzene molecule.
Keywords: Quantum Mechanics; supersymmetry; bidimensional systems; Schrodinger equation